2008
DOI: 10.1007/s10658-008-9348-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological delineation of Longidorus poessneckensis Altherr, 1974 (Nematoda: Dorylaimida)

Abstract: The plant-parasitic nematode Longidorus poessneckensis from the Czech Republic was morphologically and molecularly characterised. Molecular analyses were carried out using mitochondrial DNA (cytochrome c oxidase subunit 1-cox1) and ribosomal DNA (ITS2-second internal transcribed spacer, 18S gene and D2/D3 expansion segments of the 28S gene), which were amplified and sequenced. Phylogenetic relationship of L. poessneckensis with three morphologically closely related species, i.e. L. macrosoma, L. helveticus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…Though these nematodes are economically important pests, therefore an extensive study of these nematodes is being carried out in the Czech Republic. Previous surveys yielded six known species (Longidorus elongatus, L. euonymus, L. helveticus, L. intermedius, L. leptocephalus, L. poessneckensis) of genus Longidorus in the Czech Republic (Erbenová, 1977, Kumari & Decreamer 2007Kumari et al, 2009;Kumari & Subbotin, 2012). During recent nematological surveys L. caespiticola Hooper, 1961 was found only at one site for the first time in the Czech Republic.…”
Section: Introductionmentioning
confidence: 99%
“…Though these nematodes are economically important pests, therefore an extensive study of these nematodes is being carried out in the Czech Republic. Previous surveys yielded six known species (Longidorus elongatus, L. euonymus, L. helveticus, L. intermedius, L. leptocephalus, L. poessneckensis) of genus Longidorus in the Czech Republic (Erbenová, 1977, Kumari & Decreamer 2007Kumari et al, 2009;Kumari & Subbotin, 2012). During recent nematological surveys L. caespiticola Hooper, 1961 was found only at one site for the first time in the Czech Republic.…”
Section: Introductionmentioning
confidence: 99%
“…), the Rivers Bodrog, Latorica, Tisa and other rivers in Slovakia (Lišková & Sturhan, 2000;Lišková, 2001;Lišková & Čerevková, 2005) and in Germany in soils near or along numerous ri-vers and small brooks (Altherr, 1974;Rau, 1975Rau, , 1976Sturhan, 1995;Sturhan & Loof, 1995). The most recent information is from the Czech Republic (Kumari et al, 2009) where the species has been found in the rhizosphere of Quercus forest on a plain, probably with higher and fluctuant tailwater level. Surprisingly, this species was found in a soil sample collected from the Betuleto-Carpineto-Quercetum forest on … the small upland plain on the top of Dariusova hora hill near the city of Košice in eastern Slovakia.…”
Section: Introductionmentioning
confidence: 99%
“…Ribosomal and mitochondrial DNA sequences (accession numbers EF614265, EF614266, EF614267 and EU444017) of ♀2 (see Fig. 1) are studied by Kumari et al (2009). Lately, six normal females were sequenced from three populations from the Czech Republic.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements and photographs were taken from the temporary mounts and slides were dismantled immediately. DNA was prepared from one specimen (Kumari et al, 2009) of X. vuittenezi and another specimen of X. vuittenezi and a single specimen of X. diversicaudatum were preserved in water at -70 °C for future molecular study. Identification was made using an Olympus BX-51 light microscope, equipped with a digital camera C4040 and differential interference con-...... trast (DIC, Nomarski).…”
Section: Methodsmentioning
confidence: 99%